Concern for others: A management attribute of excellent companies - R. Khumalo (South African Journal of Business Management, 2001)
This paper examines concern for others as an attribute prevalent and commonly engaged in by the most successful companies in Zimbabwe. The attribute has been identified to be, among others, characteristic of these excellent companies and it is possible that the success of these companies is partly attributable to this characteristic. Although it is likely that this attribute contributes to successful performance by companies that apply it, there is a possibility that the achievement of this could be most effective if all the attributes including those that are not discussed here are implemented collectively resulting in a synergistic effect. The singular application of this attribute, concern for others, should nevertheless, be tried by business practitioners because it could offer significant improvements to enterprises of all kinds.
Keywords: 650